Assessment of Bone Regeneration Outcomes Using Bioactive and Standard Membranes in Dental Implant Procedures: A Clinical and Histomorphometric Study - Usman Manzoor Warraich, Muhammad Tariq Fayyaz, Mahnoor Waheed, Ammar Abdullah Malik, Umar Farooq Khan, Asrar Ahmed, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Adequate bone volume and quality are essential for successful dental implant therapy, and these arefrequently repaired using barrier membrane-assisted guided bone regeneration (GBR). Beyond passivespace maintenance, recent developments in bioactive membranesseek to stimulate osteogenesis; nevertheless,